Advance Care Planning: A Community Engagement Value Based Approach. Issue 1 (1st June 2011) - Robinson, C; Fulton, T; Collins, D; Lacasse, B; Wren, A M; Myers, L; Nicol, Judy; Thompson, Jennifer
Abstract : This workshop focuses on the design and ongoing implementation of an innovative advance care planning (ACP) initiative in one Canadian Health Authority. The initiative took a values based, community engagement approach to developing an ACP program in two communities. Developmental evaluation systematically informs the emerging programs. The initiative is in its second year and successes to date include: a shift in the relationship between the health authority and participating communities in response to a new way of 'doing business' where change is not mandated from the 'top down' but emerges 'in the middle' through active collaborative engagement; capacity development within both the health authority organizational team and the participating communities; a community specific vision of ACP that is broader than health care decision making; and, a comprehensive education program for ACP facilitators. This innovative approach has been challenging to enact in a system where a traditional policy based orientation to program development and outcomes based evaluation are the norm. Instead, success has been determined via real time decision making that aligns with the values framework underpinning the project. Multiple course corrections have occurred such as adopting developmental evaluation and moving away from an evaluative logic model. The responsive, values based process will be discussed, strengths and challenges identified and successes highlighted.